Influence of Residual Renal Function in Carotid Modeling as a Marker of Early Atherosclerosis in Dialysis Patients. Issue 5 (17th July 2017) - Rroji, Merita; Spahia, Nereida; Seferi, Saimir; Barbullushi, Myftar; Spasovski, Goce
Abstract: Atherosclerosis is frequently present in patients with chronic kidney disease (CKD) treated with dialysis. We evaluated the association between residual renal function (RRF), phosphate level, inflammation and other risk factors in carotid modeling as a marker of early atherosclerosis in peritoneal dialysis (PD) compared with hemodialysis (HD) patients. We studied 39 stable PD and 53 HD patients on renal replacement therapy (RRT) for 3 to 36 months duration. B‐mode ultrasonography was used to determine carotid artery intima media thickness (CIMT). We classified patients with atherosclerosis if they have CIMT >10 mm and or presence of plaque. Out of our total dialysis population studied of 92 patients, 16.3% were diabetics and 57.6% were on hemodialysis. Expectedly, PD patients had a higher RRF ( P <  0.001), 24 h urine volume ( P <  0.001); C‐reactive protein ( P =  0.047), and a lower serum phosphate ( P =  0.01), PTH ( P <  0.05), alkaline phosphatase ( P <  0.05), and albumin levels ( P <  0.001) compared to hemodialysis patients. Atherosclerosis was found in 66.3% of patients and in 100% of a diabetic population. There was no significant difference in the presence of atherosclerosis between PD and HD patients [56.4 vs 73.6% HD, respectively]. Multiple regression analysis showed age, diabetes, HD modality, RRF, phosphate, PTH and pulse pressure as independent parameters associated with atherosclerosis. Apart from the traditional risk factors like age and diabetes, our study showed a link of atherosclerosis with metabolic abnormalities secondary to renal failure. We demonstrated a novel, independent association between RRF and atherosclerosis, underlining the importance of preservation of the RRF in dialysis patients.